Bioassay-guided fractionation and antihypertensive properties of fractions and crude extracts of Peristrophe bicalyculata (retz) nees - Mansurah A. Abdulazeez (2018)
Hypertension is an important public health issue in both developed and developing countries due to its high incidence and morbidity. This has motivated researchers especially in developing countries to search for strategies for the treatment using different plant parts. The use of the aqueous decoction of the leaves of Peristrophe bicalyculata in the treatment of hypertension has been documented. This study was designed to carry out a bioassay-guided isolation of the antihypertensive components of the leaves of Peristrophe bicalyculata in L-NAME hypertensive rats, determine the angiotensin-converting enzyme inhibitory activity of the extracts and fractions obtained and identify the constituent(s) present. From our results, L-NAME hypertensive rats given the cold water extract had significantly (p < 0.05) lower mean arterial blood pressure (MABP) with longer duration of action than other extracts. Also, the angiotensin-converting enzyme inhibitory activity of the cold water extract was significantly (p < 0.05) higher than that of other extracts. From the GC-MS analysis of the most effective fraction (fraction 4), P,P,P-triphenyl-imino(triphenyl)phosphorane and andrographolide 2(3H)-furanone were identified among others. The present work demonstrates the hypotensive effect of the cold water extract of Peristrophe bicalyculata on L-NAME hypertensive rats, which further justifies the folkloric application of extracts of the plant in the management as well as treatment of hypertension.